The effect of serum matrix and gender on cortisol measurement by commonly used immunoassays. (May 2014) - Dodd, AJ; Ducroq, DH; Neale, SM; Wise, MP; Mitchem, KL; Armston, A; Barth, JH; El-Farhan, N; Rees, DA; Evans, C
Background: Considerable intermethod bias has been observed between cortisol immunoassays, with some also displaying a gender difference. Cortisol immunoassay performance is affected by serum matrix effects such as changes in steroid binding proteins and presence of interfering steroids which can be altered in various clinical settings. This study investigates cortisol immunoassay bias in pregnancy, renal failure and intensive care patients. Methods: Serum remaining after routine analysis from pregnant patients, patients on the intensive care unit and patients with renal failure were obtained prior to disposal and used to create 20 anonymous samples per group. A male and female serum pool was prepared and spiked with cortisol. Samples were aliquoted and distributed to four hospitals for cortisol analysis by immunoassays from four different manufacturers. Cortisol was also measured by an isotope dilution-gas chromatography–mass spectrometry method for comparison of assay bias. Results: Differences in cortisol immunoassay bias were observed across the different patient groups. A negative bias compared to pooled serum samples was observed for pregnancy serum, whilst a more positive bias was seen in renal failure and intensive care patients. Variation in bias was greatest in renal failure with the Roche E170 the most affected and the Abbott architect the least (interquartile ranges 44% and 14%, respectively). Conclusions: Cortisol immunoassay bias may be affected by gender and differences in serum matrix from patients with various clinical conditions. Users of cortisol assays should be aware of differing matrix effects on their assay and the relevance of these for the interpretation of clinical results.